Penentuan Pembukaan Gerai dengan Menggunakan Analytic Hierarchy Process Empat Layer - Muhammad Dzulfikar Fauzi; Granita Hajar; Abdul Kholik (STMIK Budi Darma, 2022)
In the neighborhood, there is a slew of flavored drink shops. Bubble drinks, sometimes known as